Graphene laminate and its preparation method and application

Through the coordinated treatment of annealing at 1000°C and mechanical compression of 150°C and 5MPa mechanical compression, the problems of high energy consumption and environmental pollution of the existing graphene laminate preparation methods are solved, and its mechanical properties and electromagnetic shielding performance are significantly improved, meeting the high-performance needs of flexible electronic equipment.

CN113939173BActive Publication Date: 2025-04-29SHENZHEN HANKE NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111216387.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-19
Publication Date
2025-04-29
Estimated Expiration
2041-10-19

AI Technical Summary

Technical Problem

The existing preparation methods of graphene laminates have problems of high energy consumption and environmental pollution, and their mechanical properties and electromagnetic shielding efficiency are not sufficient to meet the needs of large-scale production and practical applications.

Method used

By annealing at 1000°C and co-processing of 150°C and 5MPa mechanical compression, graphene laminates with excellent mechanical properties, electrical properties and electromagnetic shielding performance were prepared.

Benefits of technology

The tensile strength, bending modulus and conductivity of graphene laminates are significantly improved, and the electromagnetic shielding efficiency reaches 40dB, meeting the high-performance needs of flexible electronic equipment, while reducing production costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113939173B_ABST
    Figure CN113939173B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of graphene technology, and particularly relates to a graphene laminate and a preparation method and application thereof, comprising a step of annealing at 1000°C, and a step of subjecting a graphene foil to mechanical compression at 150°C and 5MPa to obtain a graphene laminate, wherein the annealing and mechanical compression are performed simultaneously. The prepared graphene laminate has a tensile strength of 62MPa, a bending modulus of 11GPa, and a Young's modulus of 25GPa. The maximum electrical conductivity of a 15μm thick graphene laminate can reach 82790S / m, and the electromagnetic shielding effectiveness of a 15μm thick graphene laminate can reach 40dB under a 0.8-2.6GHz test environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphene, and in particular relates to a graphene laminate and a preparation method and application thereof. Background Art

[0002] Modern electronic products with high integrated circuits have generated serious electromagnetic radiation with their rapid development, which has become a serious environmental problem due to its adverse effects on device performance and the surrounding environment. Therefore, great efforts have been made to develop high-performance electromagnetic interference (EMI) shielding materials, especially the integration of low-weight, ultra-flexible materials with excellent EMI shielding effects. These needs are particularly important in the fields of next-generation automobiles, portable electronics, and wearable devices, because multiple electronic components are packaged in a smaller area and are required to run at faster speeds, resulting in a significant increase in EMI and the failure and degradation of electronic components. Excellent EMI shielding materials must have the ability to reduce unnecessary radiation while protecting components from external signals. The main function of shielding materials is that they have high conductivity because they need to use charge carriers that interact directly with electromagnetic (EM) fields to reflect radiation. It is also worth noting that during use, electronic components in portable and flexible electronic devices generate a lot of heat, which is difficult to release and easily degrades the performance of electronic components, and may also affect the function of nearby components. Therefore, materials with excellent EMI shielding effects, high flexibility, and high thermal conductivity are very important.

[0003] Graphene, one of the most intensively studied two-dimensional carbon allotropes, consists of a layer of conjugated carbon atoms arranged in a honeycomb lattice and has excellent electrical conductivity (6000·S·cm -1 ) and high thermal conductivity (5300·W·m -1 ·K -1 ). The single-layer structure gives graphene flexibility. These unique properties make graphene a promising alternative building block for fabricating highly thermally conductive, excellent EMI shielding, and flexible interfacial macromaterials for next-generation portable devices. Early reports indicate that dispersing graphene in a polymer matrix can increase the effective thermal and electrical conductivity of the composite, thereby improving EMI shielding effectiveness. However, the thickness of composite films with 5-15wt% loading is between 1 and 3 mm, making them unsuitable for flexible electronic devices. Carbon-based foam composites have also shown high performance EMI shielding, however, the manufacturing of these foams involves complex template and etching manufacturing processes that are not suitable for large-scale production.

[0004] A potential alternative approach is based on the manufacture of laminated flexible graphene oxide (GO) films. From an application point of view, this free-standing laminate appears to be an effective material, mainly because GO films have excellent mechanical strength and flexibility, and the electrical and thermal properties can be controlled by partial high-temperature reduction. The combination of these factors makes reduced GO laminates a material with great potential for EMI shielding and thermal management. However, the prior art generally uses Hummer's method to synthesize GO, which has the problems of large amounts of chemical waste and increased energy consumption, and is therefore considered incompatible with cost-effective industrial-scale production.

[0005] The conventional preparation method of GO film usually requires a thermal reduction step and a subsequent high-temperature graphitization step, in which the graphitization reaction temperature must be at least 2000°C. In addition, it has been proven in existing reports (L. Peng et al. Advanced Materials 2017) that the mechanical properties of free-standing graphene foils can be effectively improved by high pressure (about 300MPa) and a temperature close to 3000°C. However, the operating energy requirements are too high to meet the needs of large-scale production. Summary of the invention

[0006] In order to overcome the defects of the above-mentioned prior art, the technical problem to be solved by the present invention is to provide a method for preparing a graphene laminate which is energy-saving and environmentally friendly and has excellent mechanical properties and electromagnetic shielding performance.

[0007] In order to solve the above technical problems, the present invention provides a method for preparing a graphene laminate, comprising a step of annealing at 1000°C, and a step of subjecting the graphene foil to mechanical compression at 150°C and 5MPa to obtain the graphene laminate, wherein the annealing and mechanical compression are performed simultaneously.

[0008] A graphene laminate is further provided, which is prepared by the above-mentioned method for preparing the graphene laminate, wherein the graphene laminate has a thickness of 10 to 15 μm and a bending modulus of 10 to 11.2 GPa.

[0009] And provide the application of the graphene laminate in preparing a flexible battery shielding film.

[0010] The beneficial effect of the present invention is that by simultaneously annealing the graphene foil at 1000°C and mechanically compressing it at 150°C and 5MPa, the synergistic effect between the two can significantly improve the mechanical properties, electrical properties and electromagnetic shielding effectiveness of the graphene laminate. Specifically, the tensile strength of the graphene laminate prepared by the preparation method of the graphene laminate provided by the present invention can reach 62MPa, the bending modulus can reach 11GPa, the Young's modulus can reach 25GPa, the maximum conductivity of the 15μm thick graphene laminate can reach 82790S / m, and the electromagnetic shielding effectiveness of the 15μm thick graphene laminate can reach 40dB under the 0.8-2.6GHz test environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Shown is a photograph of a graphene slurry in a specific embodiment;

[0012] Figure 2 Shown is a photo of a graphene slurry printed on aluminum foil by an automatic template printer in a specific embodiment;

[0013] Figure 3 Shown is a photograph of graphene slurry printed on aluminum foil in a specific embodiment;

[0014] Figure 4 Shown is a photograph of a graphene slurry printed on a PET substrate in a specific embodiment;

[0015] Figure 5 The top view of the graphene laminate SEM inspection in the specific embodiment shown in the figure;

[0016] Figure 6 The cross-sectional picture of the graphene laminate detected by SEM in the specific embodiment shown in the figure;

[0017] Figure 7 Shown are XRD analysis diagrams of graphene laminates and HOPG prepared under different preparation conditions in a specific embodiment;

[0018] Figure 8 Shown is a stress-strain curve diagram of a graphene laminate in a specific embodiment;

[0019] Fig. 9 Shown is a SEM thickness detection picture of a rectangular strip in a specific implementation manner;

[0020] Fig.10 Shown is a SEM surface detection picture of a rectangular strip in a specific implementation manner;

[0021] Fig.11 Shown is a graph showing changes in tensile strength of graphene laminates prepared under different preparation conditions in a specific embodiment;

[0022] Fig.12 Shown is a graph showing the change in Young's modulus of graphene laminates prepared under different preparation conditions in a specific embodiment;

[0023] Fig.13 Shown is a graph showing the change in bending modulus of graphene laminates prepared under different preparation conditions in a specific embodiment;

[0024] Fig.14 The figure shows the relationship between the area density and thickness of the graphene laminate prepared under different preparation conditions in a specific embodiment;

[0025] Fig.15 Shown is a graph showing the change in thermal conductivity of graphene laminates prepared under different preparation conditions in a specific embodiment;

[0026] Fig.16 Shown is a graph showing the change in conductivity of graphene laminates prepared under different preparation conditions in a specific embodiment;

[0027] Fig.17 The graph showing the relationship between the bending radius and relative conductivity of the graphene laminate prepared under different preparation conditions in a specific embodiment is shown;

[0028] Fig.18 Shown is the XPS spectrum of the graphene laminate annealed at 1000° C. in a specific embodiment. DETAILED DESCRIPTION

[0029] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0030] The method for preparing a graphene laminate comprises the steps of annealing at 1000°C and subjecting a graphene foil to mechanical compression at 150°C and 5MPa to obtain the graphene laminate, wherein the annealing and the mechanical compression are performed simultaneously.

[0031] The specific operation of the mechanical compression is to place a pair of ultra-smooth stainless steel plates on both sides of the graphene foil and apply a pressure of 5 MPa at 150°C.

[0032] Furthermore, the graphene foil is prepared by printing graphene slurry on a carrier plate.

[0033] The carrier plate can be a glass slide or aluminum foil, or can be one of PET, PI, PC and other polymer substrates.

[0034] When a glass slide is used as a carrier plate, its surface should be cleaned with isopropyl alcohol; preferably, the thickness of the aluminum foil is 18 to 80 μm.

[0035] Furthermore, the graphene slurry is water-based graphene ink or graphene slurry with N-methyl-2-pyrrolidone as a base solvent.

[0036] Preferably, the graphene slurry comprises 8-11 wt% of graphene sheets, 88-91 wt% of N-methyl-2-pyrrolidone and 0.2-0.4 wt% of a surfactant.

[0037] The functionalized graphene sheet can be any commercially available graphene sheet, or any commercially available N / O functionalized graphene sheet, preferably a graphene sheet prepared by the following graphene sheet preparation method: S1, using commercially available graphite (extruded graphite rod for anode, purchased from Graphite Store.Com) as anode and titanium mesh as cathode, at 1 mol·L -1 Ammonium sulfate and 1 mol·L -1 Electrochemical anode stripping is carried out in a mixed aqueous solution of sodium nitrite, the static potential is 10V, and the treatment time is 4h; S2, the stripped graphite sheets are collected and vacuum filtered using HVLP02500, and after filtration, they are repeatedly washed with water and acetone, and dried at 40°C for 8h to obtain graphene sheets. It should be noted that the extruded graphite rod for the anode can be any commercially available graphite rod, and its extrusion degree can be medium or fine, and its size can be adapted to the size of the equipment used in the anode electrochemical process, and the present invention is not limited to this.

[0038] The surfactant includes but is not limited to one of SDS, SDBS and CTAB.

[0039] Specifically, the method for preparing the graphene laminate comprises the following steps:

[0040] S1, printing the graphene slurry on a carrier plate, and drying it to form a graphene film on the surface of the carrier plate;

[0041] S2, releasing the graphene film from the carrier plate, and preparing a graphene foil from the graphene film by a doctor blade coating method, and air-drying the graphene foil;

[0042] S3. Under an inert gas atmosphere, the graphene foil is simultaneously annealed at 1000° C. and mechanically compressed at 150° C. and 5 MPa to obtain a graphene laminate.

[0043] Wherein, the thickness of the graphene film is 3 to 5 mm.

[0044] Preferably, the heating rate of the annealing is 3°C / min.

[0045] The graphene laminate is prepared by the above-mentioned method for preparing the graphene laminate, wherein the thickness of the graphene laminate is 10 to 15 μm and the bending modulus is 10 to 11.2 GPa.

[0046] Application of the graphene laminate in preparing a flexible electromagnetic shielding film.

[0047] Example 1

[0048] A method for preparing a graphene laminate comprises the following steps:

[0049] S1. Using an automatic template printer (DEK Horizon03iX), the graphene slurry was printed on the surface of an aluminum foil with a thickness of 20 μm, with a printing thickness of 3 to 5 mm, and dried in a hot air oven at 150° C. for 5 h to form a graphene film on the surface of the aluminum foil;

[0050] S2, immersing the graphene film in water to release the graphene film from the surface of the aluminum foil, and using a semi-automatic blade coater (MTI Company) to prepare a graphene foil of a larger size (at least 125 mm×200 mm), and air-drying the graphene foil at a wind speed of 10 km / h for 3 h;

[0051] S3. Place the air-dried graphene foil between a pair of smooth stainless steel plates, and anneal the graphene foil at 1000°C in a tubular furnace under a nitrogen atmosphere at a heating rate of 3°C / min. Simultaneously, perform mechanical compression at 150°C and 5 MPa (press, Caver Company). The annealing and mechanical compression time is 150 min to obtain a graphene laminate with a thickness of 15 μm.

[0052] The graphene slurry is mixed by the following components: 9.7wt% graphene sheets, 10wt% N-methyl-2-pyrrolidone and 0.3wt% SDS, the graphene sheets are prepared by the aforementioned graphene sheet preparation method, and the graphene slurry is homogenized by an industrial high shear mechanical mixer with a rotating chrome-plated steel roller.

[0053] Test Example 1

[0054] Each step of preparing the graphene laminate prepared in Example 1 is photographed and displayed. Figure 1 Shown is the graphene slurry prepared in Example 1; Figure 2 , 3 Shown is graphene paste printed on aluminum foil; Figure 4 Shown is graphene paste printed on PET substrate, with the top side inset showing a freestanding graphene laminate.

[0055] Test Example 2

[0056] The graphene laminate prepared in Example 1 was subjected to top view and side view scanning electron microscope (SEM) detection, and the detection images were as follows: Figure 5 and Figure 6 As shown. Figure 5 It can be seen that the graphene sheets can be well identified on the surface of the graphene laminate. Figure 6 It can be seen that the graphene laminate is a distinct layered structure, and the preferable in-plain orientation of the graphene sheets is the result of the flow-induced alignment characteristics of the non-spherical particles suspended in the viscous liquid. In the specific preparation method of Example 1, the constant speed of the scraper produces an effective laminar flow of the graphene slurry, and the high viscosity of the graphene slurry provides the necessary shear stress. Figure 6 In the figure, because the cross section was frozen in liquid nitrogen and then broken, the graphene sheet can be seen bending downward at the edge of the cross section.

[0057] Test Example 3

[0058] The graphene laminate and HOPG (Highly oriented pyrolytic graphite) prepared in Example 1 were subjected to XRD (diffraction of x-rays) analysis, and the comparison feature was the diffraction angle. The analysis spectrum was as follows: Figure 7 As shown, it should be noted that Figure 7 The three solid lines above the dotted line representing HOPG in the figure are 1500℃, 1000℃ and as prep. from top to bottom (not part of the legend). Among them, 1500℃ represents 1500℃ annealing and 150℃, 5MPa mechanical compression; 1000℃ represents 1000℃ annealing and 150℃, 5MPa mechanical compression; as prep. represents no annealing and mechanical compression. Figure 7 It can be seen that the diffraction angle of the graphene laminate prepared in Example 1 is 0.03° smaller than that of the HOPG sample, and the position of its diffraction peak corresponds to d 002 ≈0.336 nm interlayer spacing, and see Fig.18XPS spectrum confirms that graphene laminate is composed of pure graphene sheets (pristine graphene sheets), not GO. Except the slight shift of peak position, its width is obviously larger and has some asymmetry, which shows that there is orientation and stacking disorder in the film. This diffraction pattern is very similar to the experimental results of turbostratic graphite, and generally follows the theoretical prediction of graphite with many structural deformations (see ZQLi et al. Carbon 2007, 45, 1686-1695), such as atomic layer bending, random distortion and translation, it can be reasonably assumed that there are all three types of structural distortions in our laminate, because the deposition and restacking of a single graphene sheet are purely random in nature. Therefore, the graphene laminate prepared by the graphene sheet prepared by Example 1 is structurally close to the turbostratic graphite structure.

[0059] Among them, the reduction process is usually regarded as 002 The diffraction peak shifted from 2θ≈11°, which is similar to GO, to 2θ≈26.5°, which is more similar to graphite. Figure 7 It can be seen that after annealing at 1000℃ and 1500℃, d 002 The position and width of the peaks did not change significantly, and it was also found that the microstructure of the graphene laminates that had not been annealed and mechanically compressed was not affected by the medium and high temperature annealing temperatures of 1000°C and 1500°C. The specific reason is that since the graphene laminates are composed of pristine graphene sheets, no structural and chemical reconstruction will occur at medium and high temperature annealing temperatures. Figure 7 The diffraction pattern remains almost unchanged.

[0060] Test Example 4

[0061] Based on Example 1, comparative experiments were conducted with annealing temperature (as prep. no annealing, 1000°C and 1500°C) and whether mechanical compression was performed (150°C, 5MPa) as dual variables to test the effects of annealing temperature and mechanical compression on Young's modulus, flexural modulus and tensile strength of graphene laminates. The test results are shown in Figure 1. Fig.11 , 12 , 13. The flexural modulus was measured using the three-point method of ASTM D790-02. The test results are as follows: Figure 8 ; Young's modulus and tensile strength are obtained by cutting the graphene laminate into rectangular strips (6 mm × 20 mm) using a dynamic mechanical analyzer (TA Instruments Q 800) in a controlled force mode with a preload of 0.01 N, a ramp force of 3 N / min, and a maximum of 18 N. Figure 8The thickness and surface of the rectangular strips were tested by SEM. See the test diagram for details. Fig. 9 and 10 It should be noted that Figure 8 In the non-illustration part, the one with a larger curvature of the two solid lines is 1000℃.

[0062] from Figure 8 It can be seen that the stress-strain curve starts with straightening behavior, then almost a linear elastic region, and further deformation is seen under strain. Among them, the graphene laminate without annealing and mechanical compression has an average tensile strength of 34MPa and a Young's modulus of 13.9GPa. Fig.11 It can be seen that the tensile strength of the graphene laminate after mechanical compression at 150°C and 5MPa increased by 1.5 times to 50.9MPa. Fig.11 and Fig.12 It can be seen that direct annealing at 1000°C can effectively increase the mechanical strength of the graphene laminate to 48.1 MPa and the Young's modulus to 28 GPa, which is similar to the gain obtained by the graphene laminate only after mechanical compression. Fig.11 and Fig.12 It can also be seen that after mechanical compression and direct annealing at 1000°C, the tensile strength (62.2MPa) and Young's modulus (32.4GPa) can be significantly improved, which is comparable to or even higher than that of fiber-reinforced graphene films (see SRKwon et al., ACS nano 2017, 11, 6682-6690). And when the sample is directly annealed at 1000°C alone, it does not show such strong mechanical properties, which further demonstrates the importance of mechanical compression in improving the mechanical strength of graphene laminates. The tensile strength and Young's modulus of graphene laminates depend on the foil density, see Fig.14 , Fig.14 A plot showing the area density versus thickness for all graphene laminate samples tested under the bivariate test. Fig.11 It was shown in Figure 2 that further increasing the annealing temperature did not show any further improvement in mechanical properties. Mechanical compression leads to an increase in foil density, which is directly related to an increase in mechanical strength, but due to its internal cross-linked structure, high pressure and high annealing temperature may also damage the layered structure that connects the graphene sheets internally.

[0063] See also Fig. 9 and Fig.13The graphene laminate prepared based on Example 1 (as prep) has quite good flexibility, with a bending modulus of 20.6 GPa. After mechanical compression, the graphene laminate becomes more dense and difficult to bend due to the sharp increase in bending modulus. Further annealing and compression at 1000°C can significantly improve its flexibility, with its bending modulus increasing to 11.7 GPa and 11.2 GPa respectively. The main reason is that after the annealing process, adjacent sheets can be merged into a continuous larger sheet. However, from Fig.13 It can be seen that, similar to the tensile strength and Young's modulus, further increasing the annealing temperature does not show an increase in flexibility.

[0064] Test Example 5

[0065] Based on Example 1, comparative experiments were conducted with annealing temperature (as prep. no annealing, 1000°C and 1500°C) and whether mechanical compression was performed (150°C, 5MPa) as double variables to test thermal conductivity and electrical conductivity respectively. The test results are as follows: Fig.15 and 16 .from Fig.15 It can be seen that the annealing temperature and / or mechanical compression can improve the thermal conductivity of the graphene laminate. The existing high-pressure and high-temperature annealing to prepare the graphene laminate can provide a thermal conductivity of up to 28W / mK. The main reason is that high temperature and high pressure can lead to denser mines of the graphene laminate, thereby achieving effective heat transfer. The reason why the graphene laminate of the present application has a higher thermal conductivity is that the annealing at 1000°C can further improve the thermal conductivity by repairing the edge defects of the graphene sheet.

[0066] from Fig.16 It can be seen that the conductivity of the graphene laminate (as prep.) is 18911±202.92 S / m, and the conductivity can be improved by further mechanical compression and annealing, reaching a maximum value of 82790±896.5 S / m.

[0067] Further, the bending radius and relative conductivity are plotted and analyzed, see Fig.17 As shown. Fig.17 It can be seen that at an allowable bending radius of 4 mm, the conductivity of the graphene laminate is slightly different compared to the original value.

[0068] Test Example 5

[0069] The electromagnetic shielding effectiveness test of the graphene laminate prepared in Example 1 shows that the EMI shielding efficiency of the 15 μm thick graphene laminate can reach 40 dB at 0.8 to 2.6 GHz, which is comparable to that of a millimeter thick graphene-polymer composite material. The main reason for this is that multiple internal reflections can be made within the laminated / layered structure. These internal reflections come from the internal scattering centers and interfaces or defects of the graphene laminate, thereby absorbing EM waves by scattering.

[0070] In summary, the graphene laminate provided by the present invention, its preparation method and application, by simultaneously annealing the graphene foil at 1000°C and mechanically compressing it at 150°C and 5MPa, the synergistic effect between the two can significantly improve the mechanical properties, electrical properties and electromagnetic shielding effectiveness of the graphene laminate. Specifically, the graphene laminate prepared by the preparation method of the graphene laminate provided by the present invention can have a tensile strength of 62MPa, a flexural modulus of 11GPa, and a Young's modulus of 25GPa.

[0071] The maximum electrical conductivity of a 15μm thick graphene laminate can reach 82790S / m, and the electromagnetic shielding effectiveness of a 15μm thick graphene laminate can reach 40dB under a 0.8-2.6GHz test environment.

[0072] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a graphene laminate, characterized in that: The steps include: S1, printing a graphene slurry on a carrier plate, and drying the slurry to form a graphene film on the surface of the carrier plate; the graphene slurry comprises 8-11wt% graphene sheets, 88-91wt% N-methyl-2-pyrrolidone and 0.2-0.4wt% surfactant; S2, releasing the graphene film from the carrier plate, and preparing a graphene foil from the graphene film by a doctor blade coating method, and air-drying the graphene foil; S3. In an inert gas atmosphere, the graphene foil is simultaneously subjected to 1000° C. annealing and 150° C., 5 MPa mechanical compression to obtain a graphene laminate; the specific operation of the mechanical compression is to place a pair of ultra-smooth stainless steel plates on both sides of the graphene foil and apply a pressure of 5 MPa at 150° C.; the heating rate of the annealing is 3° C. / min; The graphene laminate has a thickness of 15 μm.

2. The method for preparing the graphene laminate according to claim 1, characterized in that: The graphene slurry is water-based graphene ink or graphene slurry with N-methyl-2-pyrrolidone as a base solvent.

3. The method for preparing the graphene laminate according to claim 2, characterized in that: The surfactant is selected from one of SDS, SDBS and CTAB.

4. The method for preparing the graphene laminate according to claim 1, characterized in that: The thickness of the graphene film is 3-5 mm.

5. A graphene laminate, characterized in that The graphene laminate is prepared by the preparation method of the graphene laminate according to any one of claims 1 to 4, wherein the graphene laminate has a thickness of 15 μm and a bending modulus of 11.2 GPa.

6. Use of the graphene laminate as described in claim 5 in the preparation of a flexible electromagnetic shielding film.

Citation Information

Patent Citations

  • Preparation method of thermal conductive film based on graphene polyimide composite sponge precursor

    CN110550956A

  • Applications of engineered graphene

    CN112004962A

  • Highly oriented graphene structures and process for producing same

    US20150217538A1